PERSEPSI MAHASISWA TENTANG DESAIN IMPLEMENTASI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA - Ernesta Leha; Reyna Virginia Nona; Falentina Lucia Banda; Konstantinus Denny Pareira Meke; Lely Suryani; Philipus Nerius Supardi; Ana Maria Gadi Djou (Program Studi PGSD Universitas Flores, 2024)
The Independent Learning of the Independent Campus Policy has a goal to improve the competence of graduates, both soft skills and hard skills. Students are expected to be better prepared to meet the needs of the times and become graduates who can become future leaders of the nation with superior personalities. Experiential learning programs with flexible pathways are expected to facilitate students to develop their potential according to their talents and potential. To realize the implementation design of the Independent Learning Campus Learning Curriculum that is per the needs of the job market, the University of Flores conducted a Student Perception Survey about the Independent Learning Implementation Design for the Independent Campus at the University of Flores. The perception study conducted at the University of Flores involved the study of student perceptions of the University of Flores on MBKM Policy Implementation Design involved 4212 students from all faculties and study programs using the Survey Method. The results show that in general, students at the University of Flores are quite aware of the existence of the MBKM Policy and are willing to be involved in the MBKM program that will be run by their respective study programs.